PENETAPAN HARGA JUAL MAKANAN DI RUMAH MAKAN KAMPUNG BAKAU KOTA KENDARI PERSPEKTIF EKONOMI SYARIAH - Sari, Kiki Novita; Lestari, Niken; Ariyani, Nova (IAIN Kendari, 2023)
This research aims to describe the mechanism for determining food selling prices at the Kampung Bakau Restaurant, Kendari City and to determine the sharia economic view in determining food selling prices at the Kampung Bakau Restaurant, Kendari City. Data collection techniques in this research are by means of documentation, observation and interviews. This type of research is qualitative research, namely research that produces descriptive data in the form of written or spoken words from people and observed behavior. With the aim of getting more comprehensive, valid, reliable and objective results regarding determining food selling prices from a sharia economic perspective at the Kampung Bakau Restaurant, Kendari City.